The effect of Task-Based Instruction on students' grammar competence - Muliati Muliati (Graduate Program, University of Islam Malang, 2021)
Grammar is considered as basic foundation in learning English and becomes one of the most pivotal language elements. Task-based instruction (TBI) is a method in English teaching dealing with grammar teaching through communicative use of language. This study attempted to examine the effect of applying TBI on students’ grammar competence. This study utilized pre-experimental with one group pre-test and post-test design applied in basic program of Kampung Inggris LC. This study was carried out in five meetings namely: (1) conducting a pre-test in the first meeting; (2) giving treatments in the second, third, and fourth meetings; and (3) giving a post-test in the last meeting. The data were gathered by utilizing multiple choice grammar test, and the data analysis utilized paired sample t-test formula. The result denoted a significant distinction between pre-test and post-test with value (t= 0.000 < p=0.05). Additionally, The mean scores of the students comprised 58.82 for the pre-test and 75.82 for the postest. Therefore, TBI is effective in teaching grammar competence.